Pulmonary Tuberculosis (PTB) Prevalence & Factors in Diabetic Patients with Poor Glycemic Control In Mwanza (International Journal of Scientific Research and Management (IJSRM), 2024)
Introduction: Tuberculosis (TB) remains a global health threat. Diabetes mellitus (DM) is a critical risk factor for TB, particularly in patients with poor glycemic control. Objective: To investigate the prevalence and associated factors of newly diagnosed pulmonary tuberculosis (PTB) among poorly controlled diabetic patients in Mwanza, Tanzania. Methods: A cross-sectional study was conducted in two hospitals, enrolling adult diabetic patients with poor glycemic control. Data were collected through questionnaires, physical examinations, laboratory tests (FBG/RBG, HbA1c, GeneXpert, chest X-ray), and BMI calculation. The primary outcome was newly diagnosed PTB. Statistical analysis was performed using STATA. Results: Among 97 participants, 59.8% were male, 74.2% were under 60 years old (mean age 48 years), and 81% had HbA1c exceeding 7%. The prevalence of newly diagnosed PTB was 18.6%, of which 12.4% were GeneXpert-positive and 6.2% were clinically/radiologically diagnosed. Obesity was a significant risk factor for PTB (OR=4.4, p=0.006). Overweight and age under 60 also showed higher PTB risk. Conclusion: Diabetics with poor glycemic control, obesity, overweight, age under 60, and abnormal chest X-rays are at high risk for PTB and require screening. Early detection and control are crucial for preventing TB spread in this vulnerable population.